Insights into student perspectives regarding food fortification in a private medical and engineering college, Bhubaneswar, Odisha: a qualitative study - Kar, Sonali; Singh, Snigdha; Patnaik, Liwa; Bhowmick, Sneha (International Journal Of Community Medicine And Public Health, 2024)
Food fortification is a crucial public health intervention aimed at addressing nutrient deficiencies and improving overall health outcomes. There is need in diet enhancement as macronutrient and micronutrient deficiency can lead to malnutrition in the long run. Young adults are the budding future of the community and their perception on food fortification and its adaptation can help the policy makers to generate better ways to implement it. This review article presents findings from a qualitative exploration of awareness regarding food fortification among students in a private college in Bhubaneswar, Odisha through an academic program. Through focus group discussions (FGDs), we investigated students’ (medical and engineering) understanding of the advantages and disadvantages of food fortification. Among the medical students, 50% were aware about food fortification, 40% were in favour of it and only 10% had misconception regarding food fortification. Whereas, among the engineering students, 72.2% were aware, 45.45% were in favour and none had any misconception or myth related to food fortification. To create awareness and promote fortified food, engineering students suggested better ideas than medical students. This analysis revealed insights into perceptions, knowledge gaps, and potential strategies for enhancing awareness and promoting the adoption of fortified foods.